The crossover - Alexander, Kwame (Houghton Mifflin Harcourt, 2019)
Presents a graphic novel adaptation of Kwame Alexander's novel of the same name. Josh Bell has a talent for composing raps, and he and his twin brother Jordan are kings of the basketball court. But when the twins' close relationship begins to unravel under the strain of changes in their lives, the brothers start to realize life isn't always about winning.